Inconsistent use of terminology in whole body vibration exercise research - Lorenzen, C.; Maschette, W.; Koh, M.; Wilson, C. (Journal of Science and Medicine in Sport, 2009)
Whole body vibration exercise (WBV) intensity can be manipulated by altering the frequency of oscillations and/or its magnitude. The inconsistencies and inaccuracies reported within the literature that at times challenge the replication and advancement of whole body vibration exercise research are discussed. Although frequency is regularly reported, inconsistency exists with the definition of vibration amplitude which has been interchangeably used with other terminology by some researchers. Of primary concern is the risk of injury to participants in future research. Researchers using intensities that were incorrectly reported by previous studies may unwittingly expose participants to harmful intensities. For clarity, an argument is put forward for the standardisation of terminology and reporting of whole body exercise parameters.